Characterization, antioxidant and antibacterial activities of gelatin film incorporated with protocatechuic acid and its application on beef preservation. (November 2021) - Zhong, Chan; Hou, Peng-Fei; Li, Ya-Xing; Yang, Wen-Yu; Shu, Mei; Wu, Guo-Ping
Abstract: A novel active packaging gelatin film incorporated with protocatechuic acid (PCA) was prepared and characterized. After addition of PCA from 0.1 to 1.0%, gelatin films showed the improved extensibility and barrier properties with better elongation at break, lower water vapor permeability and UV light transmission compared with control group. Meanwhile, the higher thickness and total color difference, weaker tensile strength of these films were also found in gelatin-PCA composite films. The molecular interaction of these films between PCA and gelatin were non-covalent linkages, including hydrogen bond, hydrophobic interaction and electrostatic interaction, contributing to homogenous and smooth microstructures observed in SEM morphologies of gelatin films containing PCA of 0.1–1.0%. In addition, gelatin-PCA composite films presented the obvious antioxidant capability to scavenge DPPH radicals and the significant inhibitory effect on total viable counts of beef in chilled storage condition. Furthermore, they also exhibited strong antibacterial effects against E. coli O157:H7 and S. aureus both in vitro as well as the challenge of beef preservation in 4 °C simulation tests. These results suggested that fish gelatin-PCA composite film, as a novel active packaging film with good functional property and high biological activity, has promising application on foods preservation. Highlights: A novel fish gelatin film incorporated with protocatechuic acid was prepared. Protocatechuic acid had plastifying effect on film by non-covalent interactions. Flexibility, UV and water barrier abilities of composite film have been improved. The composite film showed antioxidant and antibacterial activities. The composite film can enhance safety and prolong shelf-life for beef preservation.